(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article talks about the issue of upbringing in a zamoavian family,about the shortcomings of children in the Aboriginal Vaun in families, taking into account the attention given to the younger generation today and the interests of the child without being indifferent to his future, the sphere of self-sufficiency on the way of life, recommendations and opportunities given by parents to.